Predictors of residual flow in embolized intracranial ruptured aneurysms at early follow-up - Serafin, Zbigniew (International Scientific Literature, Inc., 2014)
BACKGROUND: The possibility of recanalization and the need for retreatment are the most important drawbacks of intracranial aneurysm embolization. The purpose of the study was to prospectively analyze the results of early follow-up angiography of embolized ruptured aneurysms in an attempt to determine factors predicting the presence of residual flow. MATERIAL/METHODS: Evaluation included 72 patients with 72 aneurysms, which were followed-up 3 months after the treatment. Analysis of residual flow predictors included: age and gender, clinical state in Hunt-Hess scale, aneurysm localization, aneurysm three dimensions and volume, neck width, sac-to-neck ratio, initial result of embolization, number of coils used and the use of hydrogel coils and stents. RESULTS: Mean sac diameter was 6.5±3.9 mm, and mean neck width was 2.9±1.4 mm. Follow-up angiography presented residual flow in 26 aneurysms (36.1%): class 2 in 8 aneurysms (11.1%), and class 3 in 18 cases (25.0%). Stable aneurysm filling was observed in 45 cases (62.5%), progression of residual flow in 25 cases (34.7%), and regression in 2 cases (2.8%). According to ROC analysis independent predictors of residual flow were aneurysm neck diameter (AUC 0.857, 95% CI: 0.755–0.928, p<0.0001) and sac-to-neck ratio (AUC 0.817, 95% CI: 0.708–0.898, p<0.0001). Cut-off point of the ROC curve was established at 2.8 mm for neck diameter, and 1.73 for sac-to-neck ratio. CONCLUSIONS: Aneurysm neck diameter and sac-to-neck ratio are independently related to the residual flow in embolized ruptured aneurysms at early follow-up.